The Existence of the Panji Laras Training in the Present Time - Atikah Windi Afifah; Sherlynda Puspita Sari; Siti Aisyah; Jaka Bagus Bimantoro; Dinda Ayu Rahmawati; Ahmad Dimas Jihan Pangestu (CV. Sekawan Siji, 2024)
This research focuses on the origins and existence of Petilasan Panji Laras in Benculuk, Banyuwangi. This recitation is used as a punden when holding celebrations or celebrations to avoid evil and undesirable things. This Panji Laras recitation is related to the story of Panji Laras, the village boy and his pet chicken. The story of Panji Laras begins with a cock fight in the village which he always wins, until one day he goes to town to fight cocks and wins again. Not long afterward, Panji Laras' chicken fought with the King's chicken, who was none other than his biological father. This research uses historical research methods. By observing and interviewing the land owner's family (Mr. Sudirik) as a resource and using voice recordings.